Sosial Media Marketing Untuk Pengembangan UMKM - Riri Putri Dika; Vivi Puspita Sari; Pinta Medina (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2023)
Social media marketing is a marketing strategy that involves using social media platforms to promote and develop MSME businesses (Micro, Small and Medium Enterprises). The population of social media users that continues to increase, the use of social media to develop MSME businesses can be a very effective and efficient tool. Therefore, the community service team from Putra Indonesia University "YPTK" carried out community service activities for MSME business actors, especially micro businesses with the aim of educating marketing digitalization. The purpose of this research is to explore how the use of social media marketing supported the growth and development of MSME. Social media enables MSME to reach a wider audience globally. With a broad platform and active users, MSMEs can expand their market reach and attract new customers. the use of social media marketing has great potential to help the development of MSMEs. By utilizing social media platforms wisely, MSMEs can expand market reach, build relationships with customers, and promote their products or services. However, it is important for MSMEs to design the right strategy, produce interesting content, and keep abreast of trends and changes in the world of social media to achieve success in utilizing social media marketing.